Peluang, Potensi, dan Pengembangan Bisnis Bersama Komunitas Masyarakat Cinta Bogor melalui Seminar Kewirausahaan dan Pengenalan Produk - Fadhila Akmaliyah; Siti Jahroh; Lokita Rizky Megawati; Achmad Fadillah; Anita Primaswari Widhiani; Popong Nurhayati; Alfa Chasanah; Retnaningsih Retnaningsih; Febriantina Dewi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
One of the sectors that can be developed in the economic improvement of Indonesia is small and medium enterprises (SME) sector. Strengthening several important aspects that must be applied in business activities such as digital advertising, marketing strategy, accounting and taxation. The purpose of this activity is to encourage participants who do not have a business to be motivated and increased business for those who already have a business. The event was held with the business school and partnered with the Bogor Love Society (MCB). Through this activity, it is expected to motivate partners to encourage local products to be the flagship product of Bogor. Furthermore, there has been an increased motivation for participants and partners to entrepreneurship and improve the quality of their products. Keywords: business, economy, products, UKM